The effects of shock wave therapy applied on hypertrophic burn scars: a randomised controlled trial - Peter Moortgat; Mieke Anthonissen; Ulrike Van Daele; Tine Vanhullebusch; Koen Maertens; Lieve De Cuyper; Cynthia Lafaire; Jill Meirte (SAGE Publishing, 2020)
Introduction: A wide variety of non-invasive treatments has been proposed for the management of hypertrophic burn scars. Unfortunately, the reported efficacy has not been consistent, and especially in the first three months after wound closure, fragility of the scarred skin limits the treatment options. Extracorporeal shock wave therapy (ESWT) is a new non-invasive type of mechanotherapy to treat wounds and scars. The aim of the present study was to examine the objective and subjective scar-related effects of ESWT on burn scars in the early remodelling phase. Material and methods: Evaluations included the Patient and Observer Scar Assessment Scale (POSAS) for scar quality, tri-stimulus colorimetry for redness, tewametry for trans-epidermal water loss (TEWL) and cutometry for elasticity. Patients were randomly assigned to one of two groups, the low-energy intervention group or the placebo control group, and were tested at baseline, after one, three and six months. All patients were treated with pressure garments, silicone and moisturisers. Both groups received the ESWT treatment (real or placebo) once a week for 10 weeks. Results: Results for 20 patients in each group after six months are presented. The objective assessments showed a statistically significant effect of ESWT compared with placebo on elasticity ( P = 0.011, η2 P =0.107) but revealed no significant effects on redness and TEWL. Results of the clinical assessments showed no significant interactions between intervention and time for the POSAS Patient and Observer scores. Conclusion: ESWT can give added value to the non-invasive treatment of hypertrophic scars, more specifically to improve elasticity when the treatment was already started in the first three months after wound closure. Lay Summary Pathological scarring is a common problem after a burn injury. A wide variety of non-invasive treatments has been proposed for the management of these scars. Unfortunately, the reported efficacy of these interventions has not been consistent, and especially in the first three months after wound closure, fragility of the scarred skin limits the treatment options. Extracorporeal shock wave therapy (ESWT) is a relatively new non-invasive therapy to treat both wounds and scars. The aim of the present study was to examine the scar-related effects of ESWT on burn scars in the early phase of healing. The scars were subjectively assessed for scar quality by the patient and an observer using the Patient and Observer Scar Assessment Scale (POSAS). Objective assessments included measurements to assess redness, water loss and elasticity. Forty patients were randomly assigned to one of two groups, the low-energy intervention group or the placebo control group (the device simulated the sound of an ESWT treatment but no real shocks were applied), and were tested at four timepoints up to six months. All patients were treated with pressure garments, silicone and moisturisers. Both groups received the ESWT treatment (real or placebo) once a week for 10 weeks. The objective assessments showed a significant improvement of elasticity in the intervention group when compared with placebo but revealed no significant effects on redness and water loss. Results of the clinical assessments showed no differences between the groups for the POSAS Patient and Observer scores. ESWT can give added value to the non-invasive treatment of pathological scars more specifically to improve elasticity in the early phase of healing.